The Influence of Financial Performance on Profit Growth at Pt. Topabiring Trans Logistics Pangkep Regency - Ade Irma Suardy; Nasrullah; A. Tenri Syahriani (Journal JEKAMI, 2026)
This study investigates the influence of financial performance on profit growth at PT Topabiring Trans Logistik, Indonesia, during the 2019–2023 period. Financial performance is measured using three key financial ratios: Net Profit Margin (NPM), Return on Assets (ROA), and Total Asset Turnover (TATO). A quantitative research approach was employed using secondary data derived from the company's annual financial statements. The dataset was analyzed through multiple linear regression supported by classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests, followed by t-tests, F-tests, and the coefficient of determination using SPSS version 22. The findings indicate that none of the financial performance indicators significantly affect profit growth. The t-test results show that NPM (p = 0.882), ROA (p = 0.933), and TATO (p = 0.730) are all statistically insignificant at the 5% significance level. These findings suggest that changes in profitability and asset utilization were insufficient to explain variations in profit growth during the observation period. The insignificant relationships are likely attributable to the limited number of observations and the influence of external factors, including post-pandemic economic conditions, operational costs, and changes in the company's business environment. This study contributes to the financial performance literature by providing empirical evidence from the Indonesian logistics industry and highlights that profit growth is influenced by broader operational and macroeconomic factors beyond conventional financial ratios. Future research is recommended to employ larger samples, longer observation periods, and additional explanatory variables to improve the robustness and generalizability of the findings.